The Mari wedding robes as a group’s identity marker (based on the materials of the Russian Museum of Ethnography) - Aleksandra A. Pesetskaya (Финно-угорский мир, 2020)
Introduction. In traditional culture, wedding clothing is distinguished by its multifunctionality and attractiveness, as it is meant to reflect significant social changes. In a Mari wedding clothing, robes have always played a particular role of an indicator of belonging to the community. The robe’s design and decorative features played a role of a marker. Materials and Methods. The research is based on the collections of the Russian Museum of Ethnography, which has an archive of wedding caftans of the Hill and Meadow Mari, as well as a great deal of written and field sources (2010 – 2018). Results and Discussion. The article differentiates male’s and female’s wedding caftans, underlines their basic local distinctive decor features. The colour serves as the main criterion. Apart from that, there are some distinctive features in the caftans’ back part and breast area. The article singles out highly and least decorated parts of the wedding caftan, takes a look at various materials served as a basis for decoration of the most important areas of the item. The paper highlights the most “alteration-proof” parts of the caftan and underlines the features of the wedding clothing. Conclusion. A study of this clothing item is of great significance in terms of the research of changes in the Mari traditional ceremonial clothes, because as field research in the region has proved, the color of the wedding caftan keeps on varying depending on local customs and remains to be a criterion of the group’s identity.